aitan Matius 1:1-17 dengan Misi Kedatangan Kristus ke Dunia dan Upaya Penginjilan - Anna Mariana Poedji Christanti (Jurnal Missio Cristo, 2020)
Abstract: The link of Matthew 1:1-17 with the mission of Christ's coming into the world and evangelism, is a title of writing that expected to excite the evangelical spirit for believers. The compilation of the articles is based on the results of research and literature studies that explore the history of the writing, the use of terms, symbols, limitations, and the compilation of a list of related names in genealogy of Jesus Christ (Matthew 1:1-17). Furthermore, by discovering its theological meaning, we can assemble the framework of missionary proclamation of Christ's coming into the world in evangelistic efforts.